Effect of multiple-load training on the force-velocity relationship - Toji, H.; Kaneko, M. (The Journal of Strength and Conditioning Research, 2004)
The effect of training with a combination of different loads (multiple-load training) on the force-velocity and force-power relationships was examined with training programs that included maximal isometric contraction (Fmax) and concentric contraction of the elbow flexor muscles. Twenty-one male college students were placed into 3 equal training groups (G(30 + 60), G(30 + 100), and G(30 + 60 + 100)) and performed multiple-load training 3 days per week for 8 weeks. The training load was a set fraction of the maximal isometric strength (% Fmax). The G(30 + 60) group performed 6 repetitions of elbow flexion at 30 and 60% Fmax. The G(30 + 100) group performed 6 repetitions at 30% Fmax and six 5-second Fmax loads. The G(30 + 60 + 100) group performed 4 repetitions at 30 and 60% Fmax and four 5-second Fmax loads. After training, Fmax and maximal velocity significantly increased (p < 0.05) in all 3 training groups. The increases in maximal power were significantly (p < 0.05) different between the G(30 + 60 + 100) group (52.9%) and the G(30 + 100) group (24.2%). These results suggest that multiple-load training programs with 4-6 repetitions are effective for improving muscle power and velocity of the elbow flexors.